2019
DOI: 10.1002/acn3.50839
|View full text |Cite
|
Sign up to set email alerts
|

A single‐center SCN8A‐related epilepsy cohort: clinical, genetic, and physiologic characterization

Abstract: Objective Pathogenic variants in SCN8A, encoding the voltage‐gated sodium (Na+) channel α subunit Nav1.6, is a known cause of epilepsy. Here, we describe clinical and genetic features of all patients with SCN8A epilepsy evaluated at a single‐tertiary care center, with biophysical data on identified Nav1.6 variants and pharmacological response to selected Na+ channel blockers. Methods SCN8A variants were identified via an exome‐based panel of epilepsy‐associated genes for next generation sequencing (NGS), or vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 29 publications
(45 reference statements)
3
42
4
Order By: Relevance
“…This (Vanoye et al, 2014) *Non genetic origin mutations reported: Mutations described through clinical diagnosis, but the mutation type (Mendelian or de novo) were not reported, mainly due to the lack of parents to perform genotyping and difficulty in contacting the family. DII (S1) Missense NR (Butler et al, 2017b;Hewson et al, 2018;Lindy et al, 2018;Costain et al, 2019;Johannesen et al, 2019) T767I DII (S1) Missense Decreased current density Increased current amplitude provokes by voltage ramp protocol (Estacion et al, 2014;Gardella et al, 2018;Lindy et al, (Fung et al, 2015;Zhang et al, 2015;Lindy et al, 2018;Kim et al, 2019;Tsang et al, 2019;Pan and Cummins, 2020;Schreiber et al, DIII (S6)-DIV (S1) Missense NR (Pons et al, 2018;Denis et al, 2019) G1475R DIII (S6)-DIV (S1) Missense Enhanced persistent current (Hussain et al, 2016;Ortiz Madinaveitia et al, 2017;Parrini et al, 2017;Wang et al, 2017a;Gardella et al, 2018;Lindy et al, 2018;Xiao et al, 2018;Kim et al, 2019;Trivisano et al, 2019;Zaman et al, 2019;Ranza et al, 2020;Schreiber et al, 2020) G1476S DIII (S6)-DIV (S1) Missense NR (Lindy et al, 2018) I1479V DIII (S6)-DIV (S1) Missense NR (Larsen et al, 2015;Lindy et al, 2018;Schreiber et al, 2020) E1483K DIII (S6)-DIV (S1) Missense NR (Johannesen et al, 20...…”
Section: Nav16mentioning
confidence: 99%
“…This (Vanoye et al, 2014) *Non genetic origin mutations reported: Mutations described through clinical diagnosis, but the mutation type (Mendelian or de novo) were not reported, mainly due to the lack of parents to perform genotyping and difficulty in contacting the family. DII (S1) Missense NR (Butler et al, 2017b;Hewson et al, 2018;Lindy et al, 2018;Costain et al, 2019;Johannesen et al, 2019) T767I DII (S1) Missense Decreased current density Increased current amplitude provokes by voltage ramp protocol (Estacion et al, 2014;Gardella et al, 2018;Lindy et al, (Fung et al, 2015;Zhang et al, 2015;Lindy et al, 2018;Kim et al, 2019;Tsang et al, 2019;Pan and Cummins, 2020;Schreiber et al, DIII (S6)-DIV (S1) Missense NR (Pons et al, 2018;Denis et al, 2019) G1475R DIII (S6)-DIV (S1) Missense Enhanced persistent current (Hussain et al, 2016;Ortiz Madinaveitia et al, 2017;Parrini et al, 2017;Wang et al, 2017a;Gardella et al, 2018;Lindy et al, 2018;Xiao et al, 2018;Kim et al, 2019;Trivisano et al, 2019;Zaman et al, 2019;Ranza et al, 2020;Schreiber et al, 2020) G1476S DIII (S6)-DIV (S1) Missense NR (Lindy et al, 2018) I1479V DIII (S6)-DIV (S1) Missense NR (Larsen et al, 2015;Lindy et al, 2018;Schreiber et al, 2020) E1483K DIII (S6)-DIV (S1) Missense NR (Johannesen et al, 20...…”
Section: Nav16mentioning
confidence: 99%
“…A concern as we envision clinical implementation of ASO therapy is that the SCN8A (or any) transcript reduction needed to produce a meaningful effect might be variant-specific. For example, electrophysiological recordings of Na + channels containing Nav1.6-p.R1872W variant subunits exhibit increased slowly inactivating (“persistent”) current and impaired fast inactivation, but other epilepsy-associated pathogenic variants may be more severe 14 and require suppression of transcript levels to below 50% to achieve an antiseizure effect. It would be interesting to test the extent to which older mice can tolerate more aggressive targeting.…”
Section: Commentarymentioning
confidence: 99%
“…Among them, Na v 1.6 is encoded by the SCN8A gene, and widely expressed in the projection neurons of the cerebral cortex, hippocampus, and cerebellum [2]. In general, pathogenic variants (PVs) in SCN8A associated with early onset epileptic encephalopathy are de novo missense variants, and electrophysiological studies of such PVs typically reveal 'gain of function' leading to enhanced sodium current [3]. Since the first report of SCN8A-related epilepsy in 2012, more than 100 cases have been reported.…”
mentioning
confidence: 99%
“…Although focal seizures are the most common, diverse seizure types, including epileptic spasms, atypical absence, myoclonic, and generalized tonic-clonic, can present. Seizures in patients with SCN8A PVs are often controlled effectively by sodium channel blockers, such as phenytoin, carbamazepine, and oxcarbazepine, although other anti-epileptic drugs fail to control seizures [3]. Although infants with SCN8A PVs show normal or mildly delayed development prior to seizure onset, the majority of patients have apparent developmental delay or regression after seizure onset.…”
mentioning
confidence: 99%
See 1 more Smart Citation